High‐Temperature Ternary Oxide Phases in Tantalum/Niobium–Alumina Composite Materials. Issue 8 (17th August 2022) - Eusterholz, Michael K.; Boll, Torben; Gebauer, Julian; Weidner, Anja; Kauffmann, Alexander; Franke, Peter; Seifert, Hans Jürgen; Biermann, Horst; Aneziris, Christos G.; Heilmaier, Martin
Abstract : Heat treatment of Ta/Nb‐alumina composite parts during fabrication or service can involve the formation of refractory oxide phases if additional oxygen is present. The joint approach of CALPHAD‐based calculations and experimental methods involving electron backscatter diffraction sheds light on why Ta‐containing composites form ternary AlTaO4, but in Nb‐containing samples only the binary compound NbO is found. Further information can be found in article number 2200161 by Michael Eusterholz and co‐workers. (Photo credit: Michael Eusterholz, Institute for Applied Materials – Materials Science and Engineering, and Julian Gebauer, Institute for Applied Materials – Applied Materials Physics, Karlsruhe Institute of Technology)